Outcomes of Twin Pregnancies in Women Age 45 or Older [30R]. (May 2017) - Gerber, Rachel; Fields, Jessica; Barberio, Andrea; Bodenlos, Kimberly; Fox, Nathan
Abstract : INTRODUCTION: Singleton pregnancies in well-selected women 45 and older undergoing assisted reproduction have a high likelihood of successful pregnancies with an increased risk of hypertensive disorders of pregnancy. Our objective was to investigate outcomes of twin gestations in women age 45 or older. METHODS: Historical cohort of 97 women age 45 or older with twin gestations cared for by 2 referral centers between 2005-2016. Analysis included baseline demographic and clinical characteristics. Pregnancy outcomes included gestational age at delivery, hypertensive disease in pregnancy, gestational diabetes, and IUGR. Univariate analysis of association between patient characteristics and outcomes were performed using student t-test and chi square. RESULTS: Mean maternal age at delivery was 47.7 +/- 2.0 with 99% undergoing IVF and 95.9% using donor egg. Patients have low baseline rates of hypertension (6.2%), obesity (8.0%) and pre-gestational diabetes (1%). 40.2% of women developed preeclampsia, 45.8% developed IUGR, 14.5% developed gestational diabetes, and 13.4% had an indicated preterm birth prior to 34 weeks. On univariate analysis, No baseline risk factors were associated with the development of preeclampsia or IUGR. Women of white race had a decreased risk of indicated preterm birth < 34 weeks (8.2% vs. 29.2%, p=0.009) and a decreased risk of gestational diabetes (9.6% vs. 30.4%, p=0.014). CONCLUSION: Twin pregnancy in women age 45 or older is associated with high rates of hypertensive disease in pregnancy and IUGR but overall outcomes are reassuring. Twin pregnancy should not be discouraged in well-selected, healthy women age 45 or older simply due to age alone.